Child-friendly justice in the context of child participation in criminal procedure - Petrova, Olga V. (Journal of the Belarusian State University. Law, 2023)
The author of the article defines necessity of systematic improvement of the legal regulation of the child participation in the criminal procedure of the Republic of Belarus and the harmonisation and integration of the justice system with the child protection system. The paper points out the lack of the consistency of terminology. Child-friendly justice is considered as more acceptable definition. The author studies the substantial characteristics of the definition, identifies positive tendencies in law enforcement in the Republic of Belarus and directions of enhancing criminal justice based on a child-friendly approach.